Design and Analysis of a New Type of 3T1R Force Haptic Master Operating Parallel Mechanism - Pengcheng Zhang; Lubin Hang; Xiaobo Huang; Huibin Yang; Baojun Zhang; Lusheng Zhou; Junrong Chen; Ziyu Liu; Shisen Lin (Jixie chuandong)
The master-slave operation detection device with force haptic feedback function is an effective method to improve the online detection accuracy of the hollow bolts of reactor coolant pump （RCP） and avoid damage to human health caused by nuclear radiation. In the light of motion characteristics of the ultrasonic testing probe for the hollow bolt detection，a new type of haptic master operation parallel mechanism （4-HSOC{-Ri1//Ri2（-P（4R））//Ri3⊥Ri4-}） is constructed by the topology synthesis method of parallel mechanism based on position and orientation characteristics （POC） set. The forward and inverse kinematics of the mechanism is solved by vector equation method，and furthermore the motion characteristics and workspace of the parallel mechanism are analyzed and simulated，the work space matching analysis and experimental verification are carried out for the characteristics of the deep hole detection operation at the end. The moving platform of the master force haptic parallel mechanism possesses symmetric folding property and good rotating ability. It is suitable for deep hole vertical scanning operation and meets the requirements of the slave bolt detection device of reactor coolant pump. It provides the theoretical basis for hole matching，scanning task and motion matching of the master-slave bolt detection device for reactor coolant pump.